"A prison with extra flavours": experiences of immigrants in Swedish immigration detention centres. Issue 2 (15th June 2015) - Puthoopparambil, Soorej Jose; Ahlberg, Beth Maina; Bjerneld, Magdalena
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The immigration detention environment largely influences the health and well-being of detainees by either aggravating medical conditions or contributing to new illness. There is limited research on how detainees experience and try to cope with this environment. The purpose of this paper is to describe experiences of detainees in Swedish immigration detention centres. Design/methodology/approach – Semi-structured interviews were conducted in three detention centres with a total of 21 detainees who had been detained for at least two weeks. Interview transcripts were analysed using thematic analysis. Findings – The detainees likened immigration detention to imprisonment. They experienced lack of control over their life situation mainly through arbitrary restrictions and lack of proper response from authorities making it appear futile to seek help. This perceived lack of control forced them into passivity. Differences in amenities provided in the centres were observed and some of these were reported to assist in making detention more bearable. Research limitations/implications – This study provides only one stakeholder perspective. The perspectives of other stakeholders, such as detention staff, health care professionals and volunteers must be explored to improve understanding and mitigate the effects of detention. Originality/value – Irrespective of the better standards of detention in Sweden, the detainees considered detention as imprisonment affecting their health and well-being. If states deem detention to be necessary, improved staff-detainee interaction should be ensured through proper staff training, arbitrary restrictions within detention should be avoided and health care services should be improved.